SPECIFIC FEATURES OF THE RELATIONSHIP BETWEEN M. O. MENSHIKOV AND S. A. TOLSTAYA IN THE CONTEXT OF EVOLUTION OF THE ESSAY WRITER’S VIEWS - Krizhanovsky, Nikolay; Pavlov, Yuri; Dorofeeva, Olga (Revista Inclusiones, 2020)
The article analyzes the specific features of the relationship between M.O. Menshikov and S.A. Tolstaya reflected in the notes written by the essay writer and the countess, their correspondence, essays, and memoirs. The peculiarities of how Menshikov depicted the personality of Tolstaya are described. The research shows how the perception of Tolstaya by the essay writer was changing in close connection with his comprehension of L.N. Tolstoy’s personality and writings and the evolution of his views. The article adds to the image of the writer’s wife; based on her diary entries it is pointed out that Menshikov’s essays were of great interest to the whole Tolstoy family and were read out loud in the family circle up to 1916.